(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2024)
This study discusses laws related to liquor in Malaysia based on individual rights and public interest. Although Malaysia has its liquor laws. The law has not fully succeeded in reducing damaged caused by alcohol consumption. In 2020, deaths caused by drunken drivers increased, leading to amendments to the Road Transport Act 1987. However, these amendments are ineffective as there still seem to be alcohol-related offences and addiction happening in Malaysia. This study aims to: (i) identify the legal provisions related to liquor in Malaysia; (ii) identify human rights issues arising from liquor-related laws in Malaysia; (iii) analyze the legal approaches taken by Norway to curb alcohol-related issues; and (iv) propose legal improvements to control the consumption and sale of liquor in Malaysia. To achieve these objectives, this study uses a pure and qualitative doctrinal legal approach. Information for this study was obtained from statutes, and legal cases as primary sources. The results of this study indicate that amendments need to be made to the law so it is stringent as well as creating a license policy and criminal justice policy in the laws related to drinking alcohol. Therefore, this study will put forward some suggestions to improve liquor-related laws so that it is more effective in reducing related cases in the future. Keywords: Liquor, alcohol, laws, human rights, public interests, Malaysia Full text: PDF